CRISPR/cas9 Allows for the Quick Improvement of Tomato Firmness Breeding - Qihong Yang; Liangyu Cai; Mila Wang; Guiyun Gan; Weiliu Li; Wenjia Li; Yaqin Jiang; Qi Yuan; Chunchun Qin; Chuying Yu; Yikui Wang (Current Issues in Molecular Biology)
Fruit firmness is crucial for storability, making cultivating varieties with higher firmness a key target in tomato breeding. In recent years, tomato varieties primarily rely on hybridizing ripening mutants to produce F1 hybrids to enhance firmness. However, the undesirable traits introduced by these mutants often lead to a decline in the quality of the varieties. CRISPR/Cas9 has emerged as a crucial tool in accelerating plant breeding and improving specific target traits as technology iterates. In this study, we used a CRISPR/Cas9 system to simultaneously knock out two genes, FIS1 and PL, which negatively regulate firmness in tomato. We generated single and double gene knockout mutants utilizing the tomato genetic transformation system. The fruit firmness of all knockout mutants exhibited a significant enhancement, with the most pronounced improvement observed in the double mutant. Furthermore, we assessed other quality-related traits of the mutants; our results indicated that the fruit quality characteristics of the gene-edited lines remained statistically comparable to those of the wild type. This approach enabled us to create transgenic-free mutants with diverse genotypes across fewer generations, facilitating rapid improvements in tomato firmness. This study offers significant insights into molecular design breeding strategies for tomato.